(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The article examines the role of digital educational resources in education and their impact on the development of society as a whole. The ways and possibilities of optimizing physics teaching based on digital resources are shown. The importance of digital educational resources for obtaining quality education is shown. In this work, it was proposed to use digital educational resources to study a section of the general physics course for students. It is shown that a digital educational resource can fully provide knowledge, assimilation and consolidation of educational material and will contribute to the training of qualified personnel in the field of natural sciences.